ESTIMASI INVESTASI DAN IMPLIKASINYA TERHADAP PERTUMBUHAN EKONOMI PROVINSI RIAU - Ulinni’mah, Kusuma; Panjawa, Jihad Lukis; Sari Islami, Fitrah; Septiani, Yustirania (Center for Economic Studies Universitas Katolik Parahyangan, 2025)
Economic growth is closely related to investment. Economic growth in Riau Province is still relatively low with high and fluctuating investment. Although investment levels continue to increase, economic growth is not always commensurate. This shows the potential for inefficiency in the allocation and use of investment. This study aims to analyze the value of ICOR and its efficiency needed in 2024-2026 and the relationship between investment and economic growth in Riau province. The method used descriptive quantitative methodology with secondary data in the form of time series. The analytical tools used are Incremental Capital Output Ratio (ICOR) analysis and Vector Error Correction Model (VECM). From the research results, it was found that the average ICOR value of Riau is still high, which is more than 3-4, indicating that investment in Riau Province is still not efficient. Investment needs in 2024-2026 have increased along with the amount of economic growth targets that have increased. The long-term causal relationship between investment and economic growth in Riau Province only goes in one direction, namely investment towards economic growth and not vice versa. Inefficient investment is related to Riau’s poor infrastructure in the region.